2013
DOI: 10.1039/c3cc46561f
|View full text |Cite
|
Sign up to set email alerts
|

Acrylic coatings with surprising antifogging and frost-resisting properties

Abstract: We report an unusually effective antifogging/frost-resisting coating based on conventional acrylic polymers. The intriguing antifogging property originated from the delicate balance between the hydrophilicity and hydrophobicity of the acrylic copolymers of 2-(dimethylamino)ethyl methacrylate and methyl methacrylate, as well as between the water-swellability of the copolymer and the cross-linked network due to ethylene glycol dimethacrylate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
96
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(105 citation statements)
references
References 23 publications
4
96
0
Order By: Relevance
“…[1][2][3][4] Over the last few decades, an extensive research studies have been reported to prevent the formation of fog and frost on solid surfaces by different approaches including superhydrophobic coatings, 5-7 superhydrophilic coatings 8,9 and combinations of both hydrophilic and hydrophobic properties in the coating. [10][11][12][13][14][15] Hydrophilic surfaces that have a water contact angle of less than 5 o exhibit excellent anti-fog properties because they allow water droplets to spread uniformly to form a thin water film, which reduces light scattering. 9,16,17 In general, superhydrophilicity can be obtained by various chemical and physical methods.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Over the last few decades, an extensive research studies have been reported to prevent the formation of fog and frost on solid surfaces by different approaches including superhydrophobic coatings, 5-7 superhydrophilic coatings 8,9 and combinations of both hydrophilic and hydrophobic properties in the coating. [10][11][12][13][14][15] Hydrophilic surfaces that have a water contact angle of less than 5 o exhibit excellent anti-fog properties because they allow water droplets to spread uniformly to form a thin water film, which reduces light scattering. 9,16,17 In general, superhydrophilicity can be obtained by various chemical and physical methods.…”
Section: Introductionmentioning
confidence: 99%
“…With this understanding, amphiphilic copolymers P(DMAEMA‐co‐MMA‐co‐VM) (PDMV) and P(DMAEMA‐co‐Styrene‐co‐VM) (PDSV) were synthesized by free radical solution polymerization (details in the Supporting Information). Compared to the previous work using P(MMA‐co‐DMAEMA), our amphiphilic copolymers had photo‐crosslinkable properties and avoided the use of chemical crosslinking agents in the preparation of antifogging coating. The self‐assembly copolymeric micelles forming in selective‐solvent dimethylformamide (DMF)/H 2 O were used as macromolecular emulsifiers and antifogging coatings.…”
Section: Introductionmentioning
confidence: 99%
“…The inorganic subjects consist of TiO2 [9] , SiO2 [10] , In2O3-SnO2 [11] , Cu2O and CuO [12] . And the organic subjects include PNIPAAm/PLLA (poly(N-isopropylacrylamide)/ poly(L-lactide)) [13] , DMAEMA/MMA (2-(dimethylamino)-ethylmethacrylate/methyl methacrylate) [14] .…”
Section: Instructionmentioning
confidence: 99%